Demethyleneberberine alleviated the inflammatory response by targeting MD-2 to inhibit the TLR4 signaling - Zhao, Yaxing; Liu, Peng; Luan, Haofan; Jiang, Hua; Xu, Yingmei; Zhang, Yuanqiang; Zhang, Yubin; Li, Ruiyan (Frontiers in Immunology, 2023)
The colitis induced by TNBS is a chronic and systemic inflammatory disease that leads to intestinal barrier dysfunction and autoimmune disorders. However, the existing treatments of colitis are associated with poor outcomes, and the current strategies still remain deep and long-time remission and prevention of complications. Recently, Demethyleneberberine (DMB) has been reported to be a potential candidate for the treatment of inflammatory reponse that relied on multiple pharmacological activities, including anti-oxidation and anti-inflammation. However, the target and potential mechanism of DMB in inflammatory response has not been fully elucidated. This study employed a TNBS-induced colitis model and acute sepsis mice to screen and identify the potential targets and molecular mechanisms of DMB in vitro and in vivo. The purity and structure of DMB was quantitatively analyzed by HPLC, MS, 1H-NMR and IR, respectively. The rats were induced by a rubber hose which inserted approximately 8 cm through the anus of the rat to inject with Trinitrobenzenesulfonic acid. Acute sepsis were constructed by injection with LPS via tail vein for 60 h. These animals with inflammation were orally administrated with DMB, Berberine (BBR) or Curcumin (Cruc) , respectively. The eukaryotic and prokaryotic expression system of Myeloid Differentiation protein-2 (MD-2) and its mutants were used to evaluate the target of DMB in inflammatory response. DMB had two free phenolic hydroxyl groups, and the purity was exceeded 99% in HPLC. DMB alleviated colitis and suppressed the activation of TLR4 signaling in TNBS-induced colitis rats and LPS-induced RAW264.7 cells. DMB significantly blocked TLR4 signaling in both MyD88-dependent and independent manners by embedding into the hydrophobic pocket of MD-2 protein with non-covalent bonding to phenylalanine at position 76 in a pi-pi T shaped interaction. DMB rescued mice from sepsis shock induced by LPS through targeting to TLR4-MD-2 complex. Taken together, DMB is a promising inhibitor of MD-2 protein to suppress the hyperactivated TLR4 signaling in inflammatory response.